Rancang Bangun Aplikasi Sistem Pakar Diagnosis Penyakit Stevens Johnson Syndrome dengan Metode Forward Chaining Berbasis Website - sugianti, dewi (KILAT, 2024)
Stevens Johnson’s syndrome is a severe allergic disease that it can cause death to a person if the action is late. SJS disease is a disease that has symptoms of abnormalities in the skin causing the skin peeling from the dermis. For the general public, lot’s of them who do not know about the disease because the initial symptoms are the same as the symptoms of common diseases such as fever, cough, headache, aches, and weakness, but if the drugs are consumed continuously and result in new symptoms in the next few weeks, such as blisters on the skin, blisters that spread to the skin and disorders of other organs such as the eyes, mouth, and digestion. So the purpose of this study is to produce a diagnosis application for Stevens Johnson syndrome and to apply a website-based forwad chaining method. The development method of an expert system uses the Expert System Development Life Cycle (ESDLC) to complete the stages in a more structured development. This application was created with the purpose of making it easier for someone to consult about drug allergy diseases and to provide knowledge of the symptoms and diseases of drug allergies.